Latvia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews economic developments in Latvia during 1993-94. During 1994, Latvia began to enjoy the fruits of its steadfast efforts to achieve macroeconomic stabilization and the transformation to a market economy. GDP grew by 2 percent, after three years of economic decline in which output is estimated to have fallen by about 50 percent. Real wages also increased in 1994, after sharp declines in earlier years. Although the unemployment rate increased to about 6 1\2 percent of the labor force, it remained well below expectations and also below unemployment rates in Western Europe.